Experimental substantiation of the composition of the gel base with hydrocortisone for use in veterinary medicine - Pul-Luzan, Viktoriia; Rukhmakova, Olga (ScienceRise: Pharmaceutical Science, 2021)
As veterinary practice shows, most often atopic dermatitis in animals manifests itself in the form of a rash (in the ears, muzzle, paws, etc.), which in turn is accompanied by itching. First of all, prescribe a single injection of glucocorticoids, or short-term therapy. Corticosteroid hormones (glucocorticoids) are one of the most powerful antiallergic drugs. They are effective in treating almost all types of allergic reactions. An appropriate dose of glucocorticoids is required to obtain a rapid effect, and the form of the drug should be convenient to use. The aim of the research. The aim of our study was experimentally substantiate the choice of the optimal gelling agent when developing a gel composition with hydrocortisone for use in veterinary medicine. Materials and methods. Physical, physico-chemical and pharmaco-technological methods were used during the experimental study. Studies were performed according to the method described in the SPhU. The rheological properties of the samples were determined using a rotary viscometer type Brookfield HB DV (USA) with spindle SC4-21. Results. As a result of the research, it was found that Aristoflex as a gelling agent in the development of a veterinary drug of local action will ensure the availability of appropriate extrusion properties (namely, easy and uniform application of animal skin, ease of use). Gels with hydrocortisone based on Aristoflex gave stable performance, which was confirmed by the results of mechanical and colloidal stability. Conclusions. The composition and technology of a hydrocortisone gel for local therapy of atopic dermatitis in animals has been developed. Aristoflex at a concentration of 1.5 % on the basis of a set of physicochemical, structural-mechanical and biopharmaceutical studies was selected as the optimal gelling agent in the drug